Sex Hormone Receptor Signals in Human Malignancies - Miyamoto, Hiroshi (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Sex steroids, including androgens, estrogens, and progestogens, are knownto have widespread physiological actions beyond the reproductive systemvia binding to the sex hormone receptors. Meanwhile, emerging evidence hasindicated that sex hormone receptor signals are involved in the outgrowth ofsome malignancies, such as prostate and breast carcinomas, as well as othersthat have not traditionally been considered as endocrine-related neoplasms. ThisSpecial Issue "Sex Hormone Receptor Signals in Human Malignancies" coversvarious aspects of the potential role of sex hormone receptors and related signalsin prostate cancer, breast cancer, and other neoplastic conditions by depictingpromising findings derived from in vitro and in vivo experiments as well as theanalyses of surgical specimens. The current observations described may thusprovide a unique insight into novel or known functions of sex hormone receptorsand related molecules.